Global Comparative Study on REDD+ story of change: Supporting district-level jurisdictional approaches in Indonesia - Nofyanza, S.; Peteru, S.; Thürer, T.; Duchelle, Amy E. (Center for International Forestry Research, 2021)
Through a strong partnership with an association of district government, Lingkar Temu Kabupaten Lestari (the Sustainable Districts Association, or LTKL), and earlier efforts to showcase the sustainability progress of subnational jurisdictions, CIFOR has continued its work on jurisdictional approaches to low-emission rural development in Indonesian districts.